Peran Servicescape Terhadap Peningkatan Loyalitas Pelanggan (Kajian Empiris terhadap Pelanggan Yumaju Coffee) - Setiawardani, Maya (Jurnal Riset Bisnis dan Investasi, 2021)
The purpose of this study was to identify the servicescape that has been built by Yumaju Coffee and the level of customers’ loyalty, and also to reveal how big the role of servicescape is in increasing customers’ loyalty. The research method used is quantitative methods, the sampling technique uses non-probability sampling with a purposive sampling approach of 100 respondents. The data was collected through a questionnaire using a Likert scale. The data were processed using SPSS, and using descriptive analysis, correlation analysis, simple regression analysis, and analysis of the coefficient of determination, and hypothesis testing. The results of this study indicate that the servicescape built by Yumaju Coffee is categorized as good and the level of customers’ loyalty is also high, and servicescape has a significant role in increasing customer loyalty by 31.8%.